Ethyl 3-oxo-2-(2,5-dioxopyrrolidin-3-yl)butanoate Derivatives: Anthelmintic and Cytotoxic Potentials, Antimicrobial, and Docking Studies - Mahmood, Fawad; Jan, Muhammad S.; Ahmad, Sajjad; Rashid, Umer; Ayaz, Muhammad; Ullah, Farhat; Hussain, Fida; Ahmad, Ashfaq; Khan, Arif-ullah; Aasim, Muhammad; Sadiq, Abdul (Frontiers in Chemistry, 2017)
The development of novel and more effective drugs is slow asthe resistance produced by pathogens.From the current scenario it can be imagine that this field of research will enter into the pre-antibiotic era. This work aims to study and evaluate the preliminary antibacterial, anthelmintic and cytotoxic potentials of ethyl 3-oxo-2-(2,5-dioxopyrrolidin-3-yl)butanoates.Among all of the four compounds, compound 2 has displayed remarkable potency with MIC values of 0.125, 0.083, 0.073 and 0.109 mg/ml against E. sakazakii, E. coli. S. aureus and K. pneumonia respectively. Compared to etoposide (LC50 9.8 µg/ml), the compounds demonstrated LC50 values from 280 to 765 µg/ml. For anthelmintic assay, three concentrations of each compound and standard drug were studied in determination of time of death of the two species. Excellent anthelmintic activity was observed by all four compounds against P. posthuma and A. gallibetter than standard albendazole. High GOLD fitness score data from docking analysis towards the targets represent better protein–ligand binding affinity and thus indicate a high propensity for all the active compounds to bind to the active site.Thepromisingin-vitro antimicrobial, anthelmintic activity and cytotoxicity data conclusively revealed that these compounds may serve as viable lead compounds for the treatment of bacterial and parasitic infections, and therefore, could help the medicinal chemists to design future chemotherapeutic agents to avoid rapid drug resistance.